PENGGUNAAN MEDIA JAM PINTAR DALAM MENINGKATKAN PEMAHAMAN KONSEP BILANGAN 1 - 20 PADA ANAK KELOMPOK B DI TK KHADIJAH WONOKROMO SURABAYA (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2017)
This research aimed to increase the learning process in understanding the concept of number 1-20 which is carried out in TK Khadijah Surabaya in group B with 20 participants included 7 sons and 13 daughters. This research is Classroom Action Research which is taken from Hopkins design. The collection data methods are observation and documentation. The solving problem to increase the comprehension of concept of number is using smart clock media. Analyzing data in this research is done to describe the change of action trough smart clock media in increasing the comprehension of the concept of number 120 of children. The used analyzing data in this research is reflection analysis based on cycles. The result showed that there is an increase in the comprehension of concept of number 1-20 group B TK Khadijah which is showed in cycle I and II. Based on this result, the comprehension of concept of number in cycle II is more than cycle I. Cycle I got percentage 58.4% while in the cycle II is 85.8%, so this research has achieved the expected level.